Effect of Conventional Thermal Processing Duration on Hydroxymethyel furfural, Antioxidant Activity, and Physicochemical Properties of Pomegranate Molasses - Khalid, Brwa (University of Thi-Qar Journal of agricultural research, 2025)
This study investigated the effect of traditional heating duration on the physicochemical characteristics, hydroxymethylfurfural (HMF) formation, antioxidant activity, and mass yield during the production of pomegranate molasses. Pomegranate juice was thermally concentrated under traditional conditions for up to 14 hours, with periodic sampling to monitor changes. Heating significantly affected all measured parameters (p < 0.05). HMF content showed a non-linear increase, with initial low values, a sharp rise between 1–3 hours, slight decline during intermediate heating, and a final increase at 12–14 hours. Importantly, HMF levels remained below the maximum allowable limit of 75 mg/kg, ensuring product safety. Polynomial regression confirmed a strong quadratic relationship between heating time and HMF concentration (R² = 0.912, p < 0.001). Antioxidant activity decreased gradually with heating, while total soluble solids and viscosity increased, and pH and moisture content decreased. These results emphasize the need to optimize traditional heating time to maximize yield and quality while maintaining HMF within safe limits.